Identification of variants in the mitochondrial lysine‐tRNA (MT‐TK) gene in myoclonic epilepsy—pathogenicity evaluation and structural characterization by in silico approach. Issue 7 (16th April 2018) - Nadeem, Muhammad S.; Ahmad, Habib; Mohammed, Kaleemuddin; Muhammad, Khushi; Ullah, Inam; Baothman, Othman A. S.; Ali, Nasir; Anwar, Firoz; Zamzami, Mazin A.; Shakoori, Abdul Rauf
Abstract: Variations in mitochondrial genes have an established link with myoclonic epilepsy. In the present study we evaluated the nucleotide sequence of MT‐TK gene of 52 individuals from 12 unrelated families and reported three variations in 2 of the 13 epileptic patients. The DNA sequences coding for MT‐TK gene were sequenced and mutations were detected in all participants. The mutations were further analyzed by the in silico analysis and their structural and pathogenic effects were determined. All the investigated patients had symptoms of myoclonus, 61.5% were positive for ataxia, 23.07% were suffering from hearing loss, 15.38% were having mild to severe dementia, 69.23% were males, and 61.53% had cousin marriage in their family history. DNA extracted from saliva was used for the PCR amplification of a 440 bp DNA fragment encompassing complete MT‐TK gene. The nucleotide sequence analysis revealed three mutations, m.8306T>C,  m.8313G>C, and m.8362T>G that are divergent from available reports. The identified mutations designate the heteroplasmic condition. Furthermore, pathogenicity of the identified variants was predicted by in silico tools viz., PON‐mt‐tRNA and MitoTIP. Secondary structure of altered MT‐TK was predicted by RNAStructure web server. Studies by MitoTIP and PON‐mt‐tRNA tools have provided strong evidences of pathogenic effects of these mutations. Single nucleotide variations resulted in disruptive secondary structure of mutant MT‐TK models, as predicted by RNAStructure. In vivo confirmation of structural and pathogenic effects of identified mutations in the animal models can be prolonged on the basis of these findings. Abstract : The nucleotide sequence analysis of mitochondrial DNA fragment of 440 bp (from 8123 to 8563 bp) with the MT‐TK gene sequence in the central region showed three point mutations including 8313G>C, 8306T>C, and 8362T>G. The mutation 8306T>C is new to literature, the other two have been reported but with reference to other diseases. The mutations identified in this study indicate the combination of normal and mutated mitochondrial DNA species in the patients indicating a heteroplasmic condition.